Sexual development in ADHD and internet pornography consumption - Privara, Michal; Bob, Petr (Frontiers in Psychiatry, 2023)
Development of sexual identity during adolescence is a major process of transition in individual life which in cases of ADHD specifically interacts with other ontogenetic, pathological and psychosocial conditions. According to recent findings growing consumption of internet pornography mainly in male ADHD population is closely related to compulsive sexual behavior and hypersexuality. Recent findings also indicate that consumption of internet pornography in ADHD individuals and other sexual activities may serve as a mood-altering "self-medication" which may help to cope with stressful events and decrease depression and anxiety. Taken together recent findings indicate that internet pornography consumption mainly in ADHD individuals is closely related to stressful experiences, anxiety, depression and identity problems in partnerships which significantly increase their vulnerability to the socalled "problematic pornography use" and other forms of addictive sexual behavior. From this developmental perspective "problematic pornography use" in ADHD individuals represents significant epidemiological problem which requires further research mainly with focus on clinical diagnostics and treatment.